Un pouvoir d’abbé en acte(s) : Raoul d’Argences, abbé de Fécamp (1190-1219) - Fabien Paquet (Tabularia)
As soon as Normandy was attached to the Royal domain, Philip II Augustus gave Royal status to all the Norman Benedictine abbots and reinforced links that existed since the XIIth century between the Capetian rulers and the Norman prelats. This moment represents a turn in the history of all the monasteries of the principality. The study of Raoul of Argences, abbot of la Trinité of Fécamp (1190-1219) has brought new light on the politics of Abbots around 1204. Following the examination of acts of this particular abbot, this article aims to show that far from being a moment of instability, the change of Royal power was a moment when abbatial authority was, in as far as the Abbey of Fécamp is concerned, reinforced. The study of the diplomatic aspects and the subject of forty-five charters of Raoul concord, and show that the political position of abbots must also be taken into consideration.